Pengaruh Harga, Kualitas Produk, dan Citra Merek terhadap Keputusan Pembelian Sepatu Brand Ventela di Kota Samarinda - Mikael Rendy Balpa; Saida Zainurossalamia ZA (MANABIS: Jurnal Manajemen dan Bisnis, 2025)
This study aims to analyze the influence of price, product quality, and brand image on the purchase decision of Ventela shoes in Samarinda City. The research employs a quantitative method with a survey approach using questionnaires distributed to 80 respondents. Data analysis techniques include multiple linear regression. The results indicate that price significantly affects purchase decisions with a coefficient value of 0.441. Product quality also influences purchase decisions, although its impact is lower, with a coefficient value of 0.101. Furthermore, brand image has a significant influence on purchase decisions with a coefficient value of 0.342. Simultaneously, these three variables explain 51% of the variance in purchase decisions, while the remaining 49% is influenced by other variables. The conclusion of this study is that price, product quality, and brand image play a significant role in influencing the purchase decision of Ventela shoes. This study provides practical implications for Ventela companies to consider competitive pricing strategies, maintain product quality, and build a strong brand image to enhance customer loyalty.